Draft genome sequence of the bacteriophage vB_Eco_slurp01. - Sazinas, Pavelas; Smith, Carrie; Suhaimi, Aqilah; Hobman, Jon L.; Dodd, Christine E.R.; Millard, A.D. (American Society for Microbiology, 2016)
Bacteriophage vB_Eco_slurp01 was isolated from porcine feces using Escherichia coli MG1655 as a host. With a genome size of 348 kb, vB_Eco_slurp01 is one of the largest bacteriophages isolated to date.